Cardiovascular and Central Nervous System Toxicity of Bupivacaine in Hypertensive and Vasopressin-deficient Rats. Issue 2 (March 1994) - Zavisca, Frank G.; Kytta, Juha; Heavner, James E.; Rosenberg, Per
Abstract : Background and Objectives: The authors compared the toxic profile of bupivacaine in Sprague-Dawley rats (normotensive, normal vasopressin turnover), spontaneously hypertensive rats (hypertensive, elevated vasopressin turnover) and Brattleboro rats (normotensive, deficient vasopressin turnover). Methods: The animals were instrumented (ECG, EEG, arterial and venous catheters, tracheostomy, and rectal thermoprobe) under 1%-1.5% halothane in oxygen. Rats were then paralyzed with pancuronium (1.0 mg/kg) intravenous and ventilated with 0.5% halothane, 30% oxygen, and 70% nitrous oxide. After a 30 minute stabilization period, bupivacaine was infused at 2 mg/kg/minute. The doses required to produce the following toxic endpoints were determined: arrhythmia, seizure, isoelectric EEG, and asystole. Systolic and diastolic blood pressure and heart rate were measured at baseline, and at each endpoint. Results: In spontaneously hypertensive rats, doses of bupivacaine producing seizure, isoelectric EEG, and asystole were equal to or higher than for the Sprague-Dawley rats. The only difference between these strains of rats, suggesting enhanced sensitivity of spontaneously hypertensive rats to bupivacaine toxicity, was a lower arrhythmic threshold and a dramatic fall in mean blood pressure in these animals during the first 5 minutes of the infusion, as opposed to a slight pressor response in the Sprague-Dawley and Brattleboro rats. However, mean blood pressure remained at a higher level in spontaneously hypertensive rats and the Brattleboro rats than in Sprague-Dawley rats throughout the infusion. For arrhythmia, the Brattleboro rats and Sprague-Dawley rats required a significantly higher dose than the spontaneously hypertensive rats. For seizure, the Brattleboro rats required a significantly higher dose than the spontaneously hypertensive and the Sprague Dawley rats. For isoelectric EEG, the spontaneously hypertensive rats required a higher dose than the Sprague-Dawley rats. For asystole, the doses of bupivacaine were not significantly different for the three strains. Conclusions: The percentage of infusion time spent in seizure activity (time of isoelectric EEG-time of seizure) during the infusion was significantly longer in the spontaneously hypertensive rats than in the Brattleboro rats and the Sprague-Dawley rats. These differences might be due, in part, to lower brain turnover of the excitatory peptide, vasopressin, which are high in the spontaneously hypertensive rats and near zero in the Brattleboro rats.